Dynamic modelling and optimisation of cryogenic systems - Rodriguez, Mariela Alejandra (2007)
This work addresses the dynamic optimisation of the cryogenic sector in a large-scale natural gas processing plant. Main attention is focused on rigorous dynamic modelling of countercurrent heat exchangers with phase change and a subsequent high-pressure separation tank. The original distributed parameter problem, which results from dynamic energy balances in countercurrent heat exchangers, is transformed into an ordinary differential system (ODE) by performing spatial discretisation with the method of lines. The entire model comprises algebraic equations for thermodynamic predictions with the Soave-Redlich-Kwong (SRK) equation of state, hydraulic and design equations. The differential-algebraic equation (DAE) optimisation problem is solved with an advanced simultaneous strategy that transforms the original problem into a large-scale nonlinear programming (NLP) problem through discretisation in time of the entire set of variables by collocation on finite elements. Model resolution provides optimal temporal and spatial profiles for pressure and temperature in heat exchangers, together with partial condensation description.